ADOPSI INOVASI PENGGUNAAN VARIETAS UNGGUL BARU PADI SAWAH (Oryza sativa L.) DI KECAMATAN CILAKU KABUPATEN CIANJUR PROVINSI JAWA BARAT - Sinta Noviyanti; Kusmiyati Kusmiyati; Dwiwanti Sulistyowati (Sekolah Tinggi Pariwisata Mataram, 2020)
Cianjur Regency is the central rice producer in Indonesia which has abundant natural resource potential. But the realization of public consumption is still less in meeting economic needs. This study aims to describe how much the adoption of innovations in the use of new high yielding varieties (VUB), analyze what factors influence the adoption of innovations, and formulate strategies to increase the adoption of innovative uses of new high yielding varieties. This research was carried out in the Chavi Subdistrict of Cianjur Regency on March 7 to June 30, 2020. The sampling technique was done by purposive sampling Jumlahing 70 respondents. The data analysis technique used is descriptive analysis, multiple linear regression analysis and Kendall's W analysis. The results showed that the adoption of innovations in the use of new high yielding lowland rice in the Chavi District of Cianjur included in the medium category with presentations (72.86%), so it is necessary an increase in the use of new high yielding rice varieties. Factors that influence the adoption of innovation are the level of education, the role of extension workers, farmer group meetings, and infrastructure. The strategy to increase innovation adoption is by conducting extension activities, demonstration demonstration plots to farmers.